Abrasive wear behaviors of high-vanadium alloy steel using the dry sand/rubber wheel apparatus. (December 2019) - Li, Haizhi; Tong, Weiping; Ma, Chang; Chen, Liqing; Zuo, Liang
The wear property of high-vanadium alloy steel was studied using a dry sand/rubber wheel testing apparatus and the microstructures and failure behaviors were analyzed by scanning electron microscopy, using commercial Cr16 as a reference material. The wear resistance of high-vanadium alloy steel (50 HRC) and high-vanadium alloy steel (65 HRC) was about 3 and 15 times higher, respectively, than that of Cr16. The macroscopic photographs of high-vanadium alloy steel show differences from images of Cr16 and other materials in four different zones on the observed wear scar. Due to the presence of the skeleton structure of the MC carbides, the serious wear zone showed evidence typical of particle rolling, with significant indentations on the surface and little directionality.